Interleukin 8 released after acute myocardial infarction is mainly bound to erythrocytes. Issue 6 (1st December 1997) - de Winter, Robbert J; Manten, Annemieke; de Jong, Ype P; Adams, Rob; van Deventer, Sander J H; Lie, Kong I
Abstract : Objective: To determine whether rapid clearance of interleukin 8 (IL-8) from plasma through binding to the erythrocyte chemokine receptor may be responsible for failure to detect IL-8 consistently after acute myocardial infarction. Design: Plasma concentrations of IL-8 were measured at frequent intervals in 43 consecutive patients. In 21 of these, erythrocyte bound IL-8 concentrations were also measured. The influence of infarct size, type of treatment, and the presence of early successful reperfusion on IL-8 release was assessed. Results: Peak IL-8 concentrations in plasma were raised in 31 of the 43 patients (68%). Median plasma IL-8 concentrations were 16.0 pg/ml (range 2.4 to 225.0 pg/ml) six hours after the onset of chest pain. Twelve hours after the onset of symptoms, plasma IL-8 concentrations had already returned to normal in 27 patients. In contrast, in 18 of 21 patients (86%), erythrocyte bound IL-8 concentrations were raised at between 6 and 30 hours, with a median peak value of 59.8 pg/ml (range 19 to 148 pg/ml). No correlation between peak creatine kinase MB and peak IL-8 (plasma or erythrocyte bound) was observed. There was a significant difference in peak plasma IL-8 concentrations between patients who underwent direct PTCA (19.4 pg/ml) and those who received conservative treatment (9.9 pg/ml; p = 0.0206), but no correlation with the presence of early successful reperfusion. Conclusions: IL-8 is released in plasma after acute myocardial infarction and subsequently binds to red blood cells, resulting in only a transient rise of plasma IL-8 and a more prolonged increase of erythrocyte bound IL-8.